Onsite coalescence behavior of whey protein-stabilized bubbles generated at parallel microscale pores: Role of pore geometry and liquid phase properties. (May 2023) - Deng, Boxin; Wijnen, Dirk; Schroën, Karin; de Ruiter, Jolet
Abstract: In the formulation of (food) foams, an excess of protein is needed to prevent instant coalescence of bubbles from happening at (sub)millisecond time scales. However, protein adsorption and its influences on coalescence stability rarely have been investigated under such conditions of short time scales and high protein concentrations . In the current study, the coalescence stability of whey protein isolate-stabilized bubbles was studied using a microfluidic device, for a wide range of process conditions, including bubble-forming pore geometries and liquid phase properties. The bubble formation time was varied via the applied pressure, and the corresponding extent of bubble coalescence was quantified via the analysis of bubble sizes obtained through high-speed recordings. The experimental results of bubble coalescence as function of bubble formation time, in the presence of various protein concentrations, were also captured in a semi-empirical model. The amount of proteins accumulating at the surface of coalescing bubbles can be derived from a mass balance, with protein adsorption towards the surface of coalescing bubbles assumed to follow a Langmuir isotherm. The model showed a good fit with the experimental results, and we found that as the protein concentration increases from 2.5 to 7.5% wt., in our device the minimum time required to stabilize bubbles decreases from 0.5 to 0.1 ms. From a practical perspective, our microfluidic device can be used as an efficient tool to capture the instant, (sub)milliseconds, behavior of bubble coalescence, providing closer insights for industrial-scale production of (food) foams that also takes place at these time scales. Graphical abstract: Image 1 Highlights: Bubble coalescence is studied via microfluidics and a semi-empirical model. Instant (0.01-2.8 ms) bubble coalescence is quantified by analysis of bubble sizes. The model relies on a mass balance of proteins adsorbed at coalescing bubbles' surface. High protein concentration is needed to stabilize bubbles within (sub)milliseconds. Device geometry can be used to tune bubble-bubble interactions and coalescence.